Rheumatic mitral stenosis with congenital bicuspid pulmonary valve and pulmonary artery aneurysm: Finding needle in a haystack using multimodality imaging! - Digvijay Nalawade; Vijay Sharma; Prakhyat Shetty; Archita Shrivastava (Heart India)
Bicuspid pulmonary valves (BPVs) and pulmonary artery aneurysms (PAAs) are infrequent occurrences, and their reported association may be either genetic or acquired.[1] We present a rare case of rheumatic mitral stenosis manifesting as a cerebrovascular accident, incidentally diagnosed with BPV and PAA using multimodality imaging.